(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article considers the importance and methods of using new pedagogical technologies in the teaching of physics in technical universities. The article examines the impact of modern teaching methods, interactive learning methods and modern technologies on physics education. Also, researches and experiments conducted with the aim of deepening students’ knowledge, developing independent thinking and increasing practical skills through new pedagogical approaches are presented.